Intention and practice on breastfeeding among pregnant mothers in Malaysia and factors associated with practice of exclusive breastfeeding: a cohort study - Shohaimi, Nurul Mursyidah; Mazelan, Majidah; Ramanathan, Kanesh; Meor Hazizi, Mai Shahira; Leong, Yan Ning; Cheong, Xiang Bin; Ambigapathy, Subashini; Cheong, Ai Theng (Public Library of Science, 2022)
Background Exclusive breastfeeding rate in Malaysia is low despite its known health benefits. This study aims to determine the prevalence of intention to breastfeed among pregnant mothers, the prevalence of exclusive breastfeeding practice after delivery, and factors associated with exclusive breastfeeding practice. Methods This was a prospective cohort study. All pregnant women at 36 weeks gestation or above from 17 antenatal health clinics in an urban district were invited to participate in the study. A self-administered questionnaire was used, encompassing sociodemographic, breastfeeding knowledge, attitude, and intention towards the practice of breastfeeding. The participants were followed up one month post-natal for their practice of breastfeeding via telephone or during their post-natal follow-up appointment. Results 483 pregnant mothers participated in the study initially. 462 (95.7%) were contactable after one month. 99.4% (459/462) of participants intended to breastfeed. 65.4% (302/462) of participants practiced exclusive breastfeeding. There was no significant association between intention and practice of exclusive breastfeeding. Multiple logistic regression analysis shows, pregnant mothers with high breastfeeding knowledge (AOR = 1.138; 95% CI 1.008–1.284) and Malay ethnicity (AOR = 2.031; 95% CI 1.066–3.868) were more likely to breastfeed their infant exclusively. Conclusions Prevalence of exclusive breastfeeding practice at one month in the studied district was 65.4%. Malay mothers and mothers with high breastfeeding knowledge were more likely to breastfeed exclusively. Thus, we recommend targeted intervention towards non-Malay mothers and increasing breastfeeding knowledge to all pregnant mothers.